Valor nutricional, fracionamento de carboidratos e proteína em feno de capim Tifton 85 sob duas alturas de corte e tempos de armazenamento - Sunahara, Samantha Mariana Monteiro (2015)
This study aimed to evaluate the dehydration curve, nutritional value, fractionation of carbohydrates and protein from grass hay Tifton 85 under two cutting heights in relation to ground level (4 and 8 cm) during 120 days of storage in a closed shed. The dehydration curve was determined using samples of the aerial part of plants in eight times. The experimental design was randomized blocks with time-divided sub plots with five replications, in which the main plots were two cutting heights (4 cm and 8 cm) and sub plots were time after cutting. In a second step we evaluated the nutritional value, fractionation of carbohydrates and protein Tifton 85 stored hay, and for it we adopted the randomized block design, in split plot scheme in time, with 2 treatments allocated in the plots: Cutting heiht at 4 and 8 cm from the ground five times in the subplots: baling, 30, 60, 90 and 120 days from hay storage, with five repetitions. The dehydration of Tifton 85 grass hay occurred at 48 hours for the different cutting heights and is considered a perfect time for drying hay. Upon cutting the Tifton 85 grass at 4 cm from the ground resulted in a dry matter yield of 5487 kg ha-1, and the same cut at 8 cm had the dry matter yield of 2721 kg ha-1. The dry matter content responded quadratically to hay storage time in both cutting heights studied, differing from the heights just in baling and at 120 days of storage. The mineral matter content did not differ between treatments. The levels of crude protein, ether extract and ADF presented quadratic behavior for both the cut at 4 cm, as for the cut to 8 cm from the ground. The NDF content increased linearly as a function of storage time, showing no difference between cutting heights. It was found that the IVDMD and IVDCW stored hay were lower than the values obtained at the time of cutting. The total carbohydrate content of the Tifton 85 grass hay responded linearly to the storage time, the cutting height at 4 cm from the ground and quadratic form to the storage time, the cutting height at 8 cm from the ground. There was a difference between the heights from 60 days of storage. The carbohydrate fraction A + B1 responded negatively linear to periods of storage evaluated in the two cutting heights and did not differ between the heights. The contents of the B2 fraction showed a positive linear response as a function of storage time, differing between cutting heights only after 90 days of storage. The fraction C responded positively linear with storage time, the cutting height at 8 cm from soil and quadratic form to the storage time, the cutting height at 4 cm from the ground, with a difference between cutting height at 90 and 120 days of storage. The concentration of soluble carbohydrates responded quadratically to the storage time in the two cutting heights studied, no statistical difference between the heights. For protein fractions there were no difference between the heights only for fraction A at 90 days of storage. Fractions A, B1, B3 and C presented quadratic behavior for both the cut at 4 cm, as for the cut at 8 cm from the ground. The B2 fraction showed a negative linear response as a function of storage time. Cutting the grass performed at 4 cm from the ground is the most suitable for hay production, as higher dry matter production and nutritional value without difference between treatments in baling. The storage for 120 days generates undesirable changes in nutritional value and in different fractions of carbohydrates and protein of hay of Tifton 85 grass